A Nomogram-Based Risk Classification System Predicting the Overall Survival of Patients With Newly Diagnosed Stage IVB Cervix Uteri Carcinoma - Yu, Wenke; Huang, Lu; Zhong, Zixing; Song, Tao; Xu, Hong'en; Jia, Yongshi; Hu, Jinming; Shou, Huafeng (Frontiers in Medicine, 2021)
Background: This study constructed and demonstrated a model to predict the overall survival (OS) of newly diagnosed distant metastatic cervical cancer (mCC) patients. Methods: The SEER (Surveillance, Epidemiology, and End Results) database was used to collect the eligible data, which from 2010 to 2016. Then these data were separated into training and validation cohorts (7:3) randomly. Cox regression analyses was used to identify parameters significantly correlated with OS. Harrell's Concordance index (C-index), calibration curves, and decision curve analysis (DCA) were further applied to verify the performance of this model. Results: A total of 2,091 eligible patients were enrolled and randomly split into training (n=1,467) and validation (n=624) cohorts. Multivariate analyses revealed that age, histology, T stage, tumor size, metastatic sites, local surgery, chemotherapy and radiotherapy were independent prognostic parameters and were then used to build a nomogram for predicting 1-year and 2-year OS. The C-index of training group and validation group was 0.714 and 0.707, respectively. The calibration curve demonstrated that the actual observation was in good agreement with the predicted results concluded by the nomogram model. Its clinical usefulness was further revealed by the DCAs. Based on the scores from the nomogram, a corresponding risk classification system was constructed. In the overall population, the median OS time was 23.0 months (95% confidence interval [CI], 20.5-25.5), 12.0 months (95% CI, 11.1-12.9), and 5.0 months (95% CI, 4.4-5.6), in the low-risk group, intermediate-risk group and high-risk group, respectively. Conclusion: A novel nomogram and a risk classification system were established in this study, which purposed to predict the OS time with mCC patients. These tools could be applied to prognostic analysis and should be validated in future studies.